Static and fatigue behaviour of ECC link slabs in reinforced concrete girder Joint-Free bridges. (July 2022) - Chu, K.; Hossain, K.M.A.; Lachemi, M.
Abstract: Engineered Cementitious Composite (ECC) has been recommended for application in bridge deck link slabs to minimize long-term life cycle costs through enhanced durability. However, ECC link slab experimental tests documented in the literature to date have been limited to steel superstructure, despite the use of reinforced concrete (RC) girders as common practice in bridge construction. RC deck girder isolated ECC link slab specimens were tested under static and fatigue load up to 400, 000 and 1, 000, 000 cycles with mean fatigue stress level varied from 40% to 55% of ultimate load. The fatigue-damaged specimens were then statically loaded to failure. Residual load, deflection, moment, rotation, stiffness, and energy absorbing of fatigued link slab specimens were compared with virgin specimens to determine the level of deterioration. Experimental results were compared with those obtained from analytical calculations for reinforced concrete girder joint-free bridges with EC link slabs.